Multifractal detrended fluctuation analysis of human gait diseases - Dutta, Srimonti; Ghosh, Dipak; Chatterjee, Sucharita (Frontiers in Physiology, 2013)
IIn this paper multifractal detrended fluctuation analysis is used to study the human gait time series for normal and diseased sets. It is observed that long range correlation is primarily responsible for the origin of multifractality. The study reveals that the degree of multifractality is more for normal set compared to diseased set. However the method fails to distinguish between the two diseased sets.